Oxygen Uptake Kinetics and Time Limit at Maximal Aerobic Workload in Tethered Swimming - Massini, Danilo A. [UNESP] (2023)
This study aimed to apply an incremental tethered swimming test (ITT) with workloads (WL) based on individual rates of front crawl mean tethered force (Fmean) for the identification of the upper boundary of heavy exercise (by means of respiratory compensation point, RCP), and therefore to describe oxygen uptake kinetics (VO2k) and time limit (tLim) responses to WL corresponding to peak oxygen uptake (WLVO2peak). Sixteen swimmers of both sexes (17.6 ± 3.8 years old, 175.8 ± 9.2 cm, and 68.5 ± 10.6 kg) performed the ITT until exhaustion, attached to a weight-bearing pulley–rope system for the measurements of gas exchange threshold (GET), RCP, and VO2peak. The WL was increased by 5% from 30 to 70% of Fmean at every minute, with Fmean being measured by a load cell attached to the swimmers during an all-out 30 s front crawl bout. The pulmonary gas exchange was sampled breath by breath, and the mathematical description of VO2k used a first-order exponential with time delay (TD) on the average of two rest-to-work transitions at WLVO2peak. The mean VO2peak approached 50.2 ± 6.2 mL·kg−1·min−1 and GET and RCP attained (respectively) 67.4 ± 7.3% and 87.4 ± 3.4% VO2peak. The average tLim was 329.5 ± 63.6 s for both sexes, and all swimmers attained VO2peak (100.4 ± 3.8%) when considering the primary response of VO2 (A1′ = 91.8 ± 6.7%VO2peak) associated with the VO2 slow component (SC) of 10.7 ± 6.7% of end-exercise VO2, with time constants of 24.4 ± 9.8 s for A1′ and 149.3 ± 29.1 s for SC. Negative correlations were observed for tLim to VO2peak, WLVO2peak, GET, RCP, and EEVO2 (r = −0.55, −0.59, −0.58, −0.53, and −0.50). Thus, the VO2k during tethered swimming at WLVO2peak reproduced the physiological responses corresponding to a severe domain. The findings also demonstrated that tLim was inversely related to aerobic conditioning indexes and to the ability to adjust oxidative metabolism to match target VO2 demand during exercise.